O przekładzie oraz współczesnej recepcji w Bułgarii powieści Chłopi Władysława Reymonta - Dimitrowa, Marineła (Postscriptum Polonistyczne, 2020)
This article is dedicated to the novel Peasants by the Polish writer Władysław Reymont. The author of the article presents a brief overview of the history of translation and the modern reception of the novel in Bulgaria.